2017
DOI: 10.1371/journal.pone.0189731
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial differences between taxonomic and trait biodiversity in a large marine ecosystem: Causes and consequences

Abstract: Biodiversity is a multifaceted concept, yet most biodiversity studies have taken a taxonomic approach, implying that all species are equally important. However, species do not contribute equally to ecosystem processes and differ markedly in their responses to changing environments. This recognition has led to the exploration of other components of biodiversity, notably the diversity of ecologically important traits. Recent studies taking into account both taxonomic and trait diversity have revealed that the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 84 publications
3
29
0
Order By: Relevance
“…To our knowledge, this is the first study comparing long‐term trends and multi‐decadal dynamics in multiple dimensions of functional community change across trophic groups and areas. Previous trait‐based studies on long‐term functional community change have focused on single organism groups separately, either zoobenthos (Gogina, Darr, & Zettler, ; Neumann & Kröncke, ; Veríssimo et al, ; Weigel, Blenckner, & Bonsdorff, ) or fish (Baptista, Martinho, Nyjtrai, Pardal, & Dolbeth, ; Barcelo, Ciannelli, Olsen, Johannessen, & Knutsen, ; Dencker et al, ; Frelat et al, ), and particularly multi‐trait compositional changes on local scale (Clare, Robinson, & Frid, ; Frid & Caswell, ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study comparing long‐term trends and multi‐decadal dynamics in multiple dimensions of functional community change across trophic groups and areas. Previous trait‐based studies on long‐term functional community change have focused on single organism groups separately, either zoobenthos (Gogina, Darr, & Zettler, ; Neumann & Kröncke, ; Veríssimo et al, ; Weigel, Blenckner, & Bonsdorff, ) or fish (Baptista, Martinho, Nyjtrai, Pardal, & Dolbeth, ; Barcelo, Ciannelli, Olsen, Johannessen, & Knutsen, ; Dencker et al, ; Frelat et al, ), and particularly multi‐trait compositional changes on local scale (Clare, Robinson, & Frid, ; Frid & Caswell, ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, ocean warming has profoundly impacted marine fish communities (Cheung, Watson, & Pauly, ; Flanagan, Jensen, Morley, & Pinsky, ; Fossheim et al, ; Wernberg et al, ). Examining spatial and temporal changes in fish communities under warming can provide insight into ecological responses to climate change, and how ecosystem structure may change in the future (Auber, Travers‐Trolet, Villanueva, & Ernande, ; Beukhof, Dencker, Pecuchet, & Lindegren, ; Dencker et al, ). Additionally, observational studies can provide robust results for understanding community dynamics and improving predictive models (Mouillot, Graham, Villéger, Mason, & Bellwood, ; Suding et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, and especially in recent years, trait-based approaches have been shown superior to taxonomic approaches for examining community assembly and ecosystem functioning (Lavorel & Garnier, 2002;Mouillot, Graham, et al, 2013;Pecuchet et al, 2017;Sakschewski et al, 2016;Weiher & Keddy, 1995). Yet, examining changes in taxonomic and trait diversity simultaneously may best describe community dynamics (Dencker et al, 2017;Monnet et al, 2014;Villéger, Miranda, Hernández, & Mouillot, 2010). For instance, changes in species composition may not lead to changes in trait diversity if loser species are replaced by species with similar traits (Clare, Robinson, & Frid, 2015;Villéger et al, 2010;White, Montgomery, Storchová, Hořák, & Lennon, 2018).…”
mentioning
confidence: 99%
“…, Dencker et al. ). As expected, we observed that areas with high species richness were more likely to present a higher morphological richness.…”
Section: Discussionmentioning
confidence: 99%
“…, Dencker et al. ; Appendix : Text S1). Finally, we compared the morphological distance (Euclidean pairwise distances of images calculated from coordinates on the first three PCs) with the taxonomical distance calculated with five taxonomic levels (Appendix : Text S1).…”
Section: Methodsmentioning
confidence: 99%